Clinical Profile of Patients Presenting with Breast Cancer in Nepal - Acharya, Sandhya Chapagain; Jha, AK; Manandhar, T (Kathmandu University Medical Journal, 2013)
Background Breast cancer is the second most common cancer in women in Nepal. Even though the evaluation and treatment of patients is done as per western guidelines, there are considerable variations in risk factors, presenting stage and prognostic factors such as receptor status. Objective To evaluate the clinical profile of patients presenting with breast cancer in Nepal. Method The study was conducted at Department of Radiotherapy and Oncology, Bir Hospital and Department of Radiation Oncology, BP Koirala Memorial Cancer Hospital, Bharatpur from 16th July 2007 to 15th June 2008 for a period of one year and 114 patients were enrolled. Detailed history, clinical examination and necessary investigations performed. Histological features including receptor status were recorded. Tumor Node Metastasis (TNM) staging system was as per American Joint Committee on Cancer (AJCC), fifth edition. Data was collected in preformed case report form and was managed using SPSS version 13. Results The incidence was high (34.2%) among perimenopausal women age ranging from 41 to 50. The majority of women presented with lump (98.2%) and others with pain (21.9%), nipple retraction (16.7%), ulceration (7.9%), discharge (7%), or symptoms of metastasis (6.1%). Regarding receptor status, the majority (64.0%) were Estrogen receptor (ER) and Progesterone receptor (PR) negative with 21.9 percent. ER+PR+, Younger women were more likely to be both ER and PR negative. Where available, Her-2 immunohistochemistry showed that 45.0 % of post menopausal women were Her-2 neative, compared to 64.0 % of premenopausal women. Incidence of Triple negative disease was 41.3 %. The most common stage at presentation was stage III (26.3%). Conclusion Majority of patients were perimenopausal, presenting with locally advanced disease (Stage III and Stage II) and with average tumor size two to five cm and were hormonal receptor negative. These findings are similar to other South Asian population but is inverse than profile reported in Western populations. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 3-7 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8009